PEMBERDAYAAN GELANDANGAN DAN PENGEMIS MELALUI BIMBINGAN VOKASI DI BALAI REHABILITASI UNIT BINA KARYA YOGYAKARTA - NOVIE PURNIA PUTRI; MUNIFATUZ ZAHRO’ (Social Welfare Study Program, 2020)
Abstract. Bum and beggars are one of the social welfare problems in Yogyakata. In the rehabilitation program for sprawl, the Bina Karya unit has a one-year program target for fifty fostered residents with an on-off system, where there is a certain period of sprawl getting fostered until the termination stage. This research discusses the empowerment of homeless people and beggars through vocational guidance at the Center of Rehabilitation of Unit Bina Karya in Yogyakarta. This type of research uses a qualitative approach. The results of this study indicate that the vocational guidance provided by Balai for flat housing includes welding, wood, sewing, and agriculture vocational guidance. In the implementation of vocational guidance has supporting and inhibiting factors. The supporting factors such as cooperation with Balai practitioners who are competent in their fields and collaborating with business units. Then the inhibiting factors include the mental and mindset of the Social Fostered Citizens (WBS) are weak, WBS rejection of guidance, lack of social workers, and vocational assessment is less in-depth. Abstrak. “Gepeng” adalah satu dari sekian masalah sosial yang ada di Yogyakarta. Dalam program rehabilitasi terhadap Gepeng, unit Bina Karya memiliki sasaran program satu tahun untuk lima puluh warga binaan dengan sistem on-off, di mana terdapat periode tertentu terhadap Gepeng untuk mendapatkan binaan sampai pada tahap terminasi. Melalui metode kualitatif, penelitian ini membahas pemberdayaan gelandangan dan pengemis melalui bimbingan vokasi di Balai Rehabilitasi Unit Bina Karya Yogyakarta. Hasilnya menunjukkan bimbingan vokasi oleh Balai terhadap gepeng meliputi bimbingan vokasi las, kayu, menjahit, dan pertanian. Dalam pelaksanaan bimbingan vokasi ada beberapa faktor pendukung dan penghambat. Faktor pendukung meliputi kerjasama Balai dengan praktisi yang kompeten dalam bidangnya dan bekerja sama dengan unit usaha. Sedangkan faktor penghambat meliputi mental dan mindset Warga Binaan Sosial (WBS) yang lemah, penolakan WBS terhadap bimbingan, kurangnya tenaga pekerja sosial, dan assessment vokasional kurang mendalam.